Implementasi IoT Cerdas Berbasis Inference Fuzzy Tsukamoto pada Pemantauan Kadar pH dan Ketinggian Air dalam Akuaponik - Adlan Jiwa Kuswinta; I Gede Putu Wirama Wedashwara W; I Wayan Agus Arimbawa (Journal of Computer Science and Informatics Engineering (J-Cosine), 2019)
The population of Mataram City amounted to 362,243 people in December 2008. The increase in population and rapid development caused a reduction in sources of clean water, especially in urban areas. In fish and plant cultivation it requires good water quality so that fish and plants are not exposed to parasites and diseases that cause fish and plants to die. Akuaponik uses water continuously from the maintenance of fish which is then distributed to plants, and then returned to the fish pond. This aquaponics system will be implemented with IoT using microcontrollers, ultrasonic sensors and pH sensors that will provide information through the website. The information will be given in the form of stability in the pH level of the water and the water level in the fish pond. Checking the stability of the pH level of the water and the height of the water is intended to maintain the plant so that it can absorb nutrients optimally from the water. One method that can be used to control pH levels based on water height by adding or reducing water is to create a system that can inform good results using fuzzy logic methods. The implementation of this system will be focused on plants using 2 different types of plants and evaluation carried out is only pattern recognition rather than optimization. To recognize patterns of change and adjust the height and pH of water in aquaponics to remain stable is to implement the concept of IoT and Inference Fuzzy Tsukamoto. The aquaponics system that is made can run well and shows information based on the results of fuzzy calculations.